Heterogenous organic metal catalyst with three-dimensional mesoporous structure, preparation method and application thereof - HEXING,ZHANG LI (2007)
The invention relates to a method for preparing three-dimension non-uniform organic metal catalyst, wherein it comprises preparing carrier; reacting the toluene solution of organic metal with carrier under argon gas for 12-48h, filtering and drying; adding catalyst into extractor to be extracted and using non-water toluene to wash until the solution is transparent, to obtain the product, whose specific area is 150-500cm3/g, aperture is 2-10nm, and capacitor is 0.4-1.0cm3/g. The invention has high activity and high selectivity.